Pos–Timor-Leste's Accession to ASEAN: Process, Challenges, and Opportunities for National Development - Rui Ximenes; Putu Eka Trisna Dewi (Jurnal Studi Pemerintahan dan Akuntabilitas, 2026)
Purpose: To analyze Timor-Leste’s accession to ASEAN as a strategic move to strengthen regional integration and enhance the country’s diplomatic role in Southeast Asia. Research methodology: A qualitative approach combined with policy analysis was used to provide an in-depth overview of the accession dynamics. Results: This study highlighted several key challenges and significant opportunities. Among the challenges identified were limited administrative capacity, uneven infrastructure development, and the need to harmonize national regulations with ASEAN standards. However, the research also recognized notable opportunities, including accelerated national development through enhanced economic cooperation, increased investment, improved regional connectivity, and a stronger role in multilateral forums. These findings emphasize the importance of addressing these challenges while capitalizing on opportunities to foster growth and strengthen the regional integration. Conclusions: Timor-Leste’s accession to ASEAN holds considerable potential for national development and regional integration but requires addressing institutional and regulatory challenges to fully maximize membership benefits. Limitations: The study is based on qualitative analysis and policy review, which may limit generalizability and depend on the availability of current data and official documents, respectively. Contributions: This Journal Article offers a comprehensive assessment of Timor-Leste’s accession process and strategic recommendations to optimize its future ASEAN membership benefits.